CHEMICAL STUDY OF THE CONTRIBUTION PHTYRUSA Pyrifolia (H.B.K) EICHLER "welding with welding» - Lau Reyna, L. (2004)
The analysis of Phtyrusa pyrifolia by methods AOAC showed the presence of steroids, phenols, tanines, cumarines and flavonoids, calcium, phosphorus, magnesium, coopper, kalium and iron.